The psychology of talent development in Paralympic sport: the role of personality - Martin, J.; Prokesova, E.; Macdougall, H. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
In the current chapter, we discuss the psychological factors linked to talent development and performance. Athletes, with their coaches` help, are often responsible for their own mental skill development as there are so few applied sport psychologists working full time, in general, and even fewer in Paralympic sport (Martin, 2017; 2019). Relative to mental skills, personality factors have received less attention in the sport psychology literature. Therefore, we discuss the five-factor model (FFM) and personality trait like individual differences (PTLID: e.g., grit) that are related to talent development in Paralympians (Martin, 2017). We then review work on how coaches, and sport psychologists can foster the growth of personality traits. We conclude with future research directions.